Putty‐Clay and Investment: A Business Cycle Analysis - Gilchrist, Simon; Williams, John C. (Journal of Political Economy, 2000)
This paper develops a general equilibrium model with putty‐clay technology, investment irreversibility, and variable capacity utilization. Low short‐run capital‐labor substitutability induces the putty‐clay effect of a tight link between changes in capacity and movements in employment and output. Permanent shocks to technology or factor prices generate a hump‐shaped response of hours, persistence in output growth, and positive comovement in the forecastable components of output and hours. Capacity constraints result in asymmetric responses to large shocks with recessions deeper than expansions. Estimation of a two‐sector model supports a significant role for putty‐clay capital in explaining business cycle and medium‐run dynamics.